2007
DOI: 10.1359/jbmr.061102
|View full text |Cite
|
Sign up to set email alerts
|

Deactivating Germline Mutations in LEMD3 Cause Osteopoikilosis and Buschke-Ollendorff Syndrome, but Not Sporadic Melorheostosis

Abstract: Autosomal dominant OPK and BOS feature widespread foci of osteosclerotic trabeculae without or with skin lesions, respectively. Occasionally, a larger area of dense bone in OPK or BOS resembles MEL, a sporadic sclerosing disorder primarily involving cortical bone. Others, finding deactivating germline LEMD3 mutations in OPK or BOS, concluded such defects explain all three conditions. We found germline LEMD3 mutations in OPK and BOS but not in sporadic MEL. Introduction:In 2004, others discovered that heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 29 publications
7
55
0
4
Order By: Relevance
“…However, another study did not find mutation in three patients with sporadic melorheostosis [12]. The exact causes remain unclear.…”
Section: Introductionmentioning
confidence: 94%
“…However, another study did not find mutation in three patients with sporadic melorheostosis [12]. The exact causes remain unclear.…”
Section: Introductionmentioning
confidence: 94%
“…drome (22) (3), X-linked hypophosphatemia (5), juvenile Paget disease (23) (4), melorheostosis (3), fibrodysplasia ossificans progressiva (3), autosomal-dominant osteosclerosis with brittle teeth (24) (10), osteomesopyknosis (2), and undiagnosed (25) (1).…”
Section: Osteopetrosis (Alt Ald Ck-bb and Tracp-5b Values)mentioning
confidence: 99%
“…Kim J-E demonstrated that there is down regulation of adhesion proteins those involved in osteoblastic regulation, specifically transforming growth factor β induced gene product, which helps in the development of hyperostosis and associated soft tissue abnormalities [9] . Another possible aetiology of melorheostosis is a loss of function mutation in the LEMD3 gene, a protein involved in bone morphogenic protein and tumor growth factor-β signalling [10] . Above mentioned both hypothesis support the genetic involvement of the disease so further work have to be done, to find out exact cause and role of gene therapy for this rare disease.…”
Section: Discussionmentioning
confidence: 99%